A randomized controlled trial comparing two cognitive-behavioral programs for adolescent girls with subclinical depression: A school-based program (Op Volle Kracht) and a computerized program (SPARX). (May 2016) - Poppelaars, Marlou; Tak, Yuli R.; Lichtwarck-Aschoff, Anna; Engels, Rutger C.M.E.; Lobel, Adam; Merry, Sally N.; Lucassen, Mathijs F.G.; Granic, Isabela
Abstract: Limited research has indicated the effectiveness of the school-based Cognitive Behavioral Therapy (CBT) prevention program 'Op Volle Kracht (OVK)' and the computerized CBT program 'SPARX' in decreasing depressive symptoms. Therefore, a randomized controlled trial of the effectiveness of OVK and SPARX was conducted among Dutch female adolescents ( n = 208, mean age = 13.35) with elevated depressive symptoms. Participants were randomly assigned to one of four conditions: OVK only ( n = 50), SPARX only ( n = 51), OVK and SPARX combined ( n = 56) and a monitoring control condition ( n = 51). Participants in the first three conditions received OVK lessons and/or the SPARX game. Depressive symptoms were assessed before interventions started, weekly during the interventions, and immediately after the interventions ended, with follow-up assessments at 3, 6 and 12 months. Intention to treat results showed that depressive symptoms decreased in all conditions ( F (12, 1853.03) = 14.62, p < .001), with no difference in depressive symptoms between conditions. Thus, all conditions, including the monitoring control condition, were equally effective in reducing depressive symptoms. Possible explanations for the decrease of depressive symptoms in all conditions are discussed and suggestions for future research are provided. Dutch Trial Register: NTR3737. Highlights: A RCT of the depression prevention effects of two CBT programs. Participants were Dutch female adolescents with elevated depressive symptoms. Depressive symptoms decreased in all conditions, including monitoring controls. No difference in depressive symptoms between conditions were found after one year. Explanations for similar decreases in symptoms in all conditions are discussed.